Trees as providers of environmental services in multifunctional landscapes are vulnerable to climate change - Jamnadass, Ramni H.; Gebrekirstos, Aster; Neufeldt, Henry; Muthuri, Catherine W.; Dawson, I.; Kindt, Roeland; Nyberg Y; Dietz, Johannes; Bayala, Jules; Kuyak, Shem; Ong CK; Sotelo Montes, Carmen; et al. (World Agroforestry Centre, 2011)
In this section we provide a more in-depth look at the role trees play in the provision of goods and services in multifunctional landscapes. Tree growth is, however, vulnerable to climate variability, depending on the physiological properties of the tree and characteristics of the site. A further quantification of climate variability and climate change is needed to advise on what types of trees can be grown where, to be ready for the likely local climate-change during their lifetime. This leads to a discussion of the two-way relationship between climate change adaptation and rewards for environmental services in multifunctional landscapes as a way to reduce vulnerability to climate change.